The Signification of LINE Stickers from the Construction of Personal Identities - ศรีเพ็ชร สมเกียรติ (Siam Communication Review, 2019)
This article aims to study the signification of LINE Stickers which were created from personal identities. The data were collected from five sets of LINE stickers, by depth-interview from creators, and analyzed thought the concepts. The study found that the meaning of LINE stickers were conveyed by images and texts, collaboratively. The photos represent the real personal identities, on the contrary, drawing images represent reduced personal identities which refer to the prototype. Finally, the texts applied in LINE stickers was informal language to make communicators mutual understanding.